Improving The Eleventh Grade Students’ Speaking Ability Through Topic Based-Paired Conversation Activity at SMA Negeri 3 Parepare - Rahmatullah Syaripuddin (La Parole : Journal of Language Teaching and Pedagogy, 2019)
This research was based on the students’ problem regarding the English teaching, especially the students’ speaking ability. It was caused by the teaching activity applied in the classroom, where the teacher was more active than the students. Consequently, the students’ speaking ability was low. Therefore, the objective of the research was to find out whether or not the use of topic based-paired conversation activity improves the eleventh grade students’ speaking ability at SMA Negeri 3 Parepare. The researcher applied quasi-experimental design, with two groups pre-test and post-test design. The population of this research was the eleventh grade students at SMA Negeri 3 Parepare academic year 2016/2017. The sample of the research was taken by using total random sampling which consisted of 56 students from two classes taken from the population of the eleventh grade students of SMA Negeri 3 Parepare, XI. IPA 2 as the experimental class and XI.IPA 1 as the control class. The result of the data analysis showed that the students’ speaking ability was improved, it was showed by the mean score of pre-test was 31.19 and the post-test was 59.82. It showed that the speaking ability of the eleventh grade students at SMA Negeri 3 Parepare improved through topic based-paired conversation activity. After analyzing the data by using SPSS version 21, the result of probability value in post-test was 0.00 and significance value was 0.05. It means that the probability value (0.00) was lower than significance value (0.05). Those indicated that H0 was rejected and H1 was accepted. It means that the eleventh grade students’ speaking ability at SMA Negeri 3 Parepare for experimental class and control class was significantly difference. In conclusion, teaching speaking through topic based-paired conversation activity was effective to improve the eleventh grade students’ speaking ability at SMA Negeri 3 Parepare of academic year 2016/2017.